Mapping the landscape: Growth and trends in ethnomathematics research – A bibliometric review - Noerhasmalina, Noerhasmalina; Hidayatulloh, Hidayatulloh (Al-Jabar: Jurnal Pendidikan Matematika, 2023)
Background: At the junction of mathematical tenets and cultural paradigms, ethnomathematics has begun to manifest its scholarly presence, exhibiting a progression marked by sporadic volatility but generally steering towards a positive direction.Aim: This bibliometric survey meticulously delineates the ethnomathematics-related publication portfolio, unearths influential scientific platforms, and spotlights the foremost contributors in the field.Method: Harnessing the capabilities of VOSviewer software, this investigation excavates the wealth of knowledge embedded within the associated articles and documents. The probe utilized the keyword "ethnomathematics", opting for "article title, abstract, keywords" from the Scopus.com database search menu.Result: Among its revelations, the year 2020 emerged as a zenith in the publication landscape with 63 radiant documents, while the "Journal of Physics Conference Series" stood as a formidable scientific source, boasting 111 documents. Authors like Herawaty, D., and Widada,., shone brightly with 15 documents apiece. The word "ethnomathematics" waved like a flag, appearing 189 times across articles with a total link strength of 80.Conclusion: This exploration draws to a conclusion that despite experiencing ebb and flow, the overall trend in ethnomathematics publication has charted a course towards positive elevation. The implications of this research voyage illuminate a path for adopting a broader approach in keyword selection, beckoning us for a deeper dive into the intricate beauty of this interdisciplinary domain. The gleaned insights reverberate as a call for further experimental and phenomenological studies, plunging into the rich and captivating cultural facets of mathematics.